Re-Mapping Archaeology : Critical Perspectives, Alternative Mappings - Gillings, Mark (Routledge, 2018)
Cover -- Title -- Copyright -- Contents -- Acknowledgements -- Contributors -- 1 On maps and mapping -- PART 1 Where do maps come from and what do they do? -- 2 The map as assemblage: landscape archaeology and mapwork -- 3 Cults of the distribution map: geography, utopia and the making of modern archaeology -- 4 Feminist mapping for archaeologists: at the intersection of practices -- PART 2 Practices of mapping -- 5 The eye of the beholder: experience, encounter and objectivity in archaeo-topographical survey -- 6 The craft of earthwork survey -- PART 3 Experimental mappings and cartographic provocations -- 7 Experimental mapping in archaeology: process, practice and archaeologies of the moment -- 8 Here be worms: map art for the archaeologist (or how I learned to stop worrying and love artistic abstraction in maps) -- 9 Describing Hermion/Ermioni. Between Pausanias and digital maps, a topology -- 10 Re-thinking the conversation: a geomythological deep map -- 11 Mapping sound: creating a static soundscape -- PART 4 Digital transformations -- 12 Archaeology, digital cartography and the question of progress: the case of Çatalhöyük (Turkey) -- 13 Cartography and quantum theory: in defence of distribution mapping -- PART 5 When all is said and done -- 14 Making maps: a commentary -- Index.